Real-time monitoring of aqueous Hg2+ reduction dynamics by magnetite/iron metal composite powders synthesized hydrothermally. (13th July 2022) - Brunet, Fabrice; Tisserand, Delphine; Lanson, Martine; Malvoisin, Benjamin; Bertrand, Mathieu; Bonnaud, Céline
Abstract: An iron-based powder material composed of zerovalent iron (8 wt.%) and magnetite (92 wt.%), has been synthesized hydrothermally at 200 °C from zero-valent iron. Its effect on the reduction of aqueous Hg 2+ into gaseous Hg 0 has been investigated at ambient conditions for pH comprised between 4 and 8.5. The production of Hg 0 was monitored with an online mercury vapor analyzer at the picogram level for concentrations of iron-based composite of a few tenths of mg L −1 . Starting from a solution having an Hg 2+ concentration of 25 ng L −1 at pH = 4, a succession of two Hg 0 production events was recorded. The first event is related to the Hg 2+ reduction by ZVI which fully dissolved within the first hours. Upon ZVI consumption, pH drifted towards the pH window where magnetite can efficiently reduce Hg 2+ at the hour timescale, resulting in a second Hg 0 production peak. The combined use of ZVI and magnetite to remove aqueous Hg 2+ by formation of Hg 0 (volatile) under mild acidic pH allows (1) to maximize the Hg 2+ reduction rate and (2) to take benefit of the longer lifetime of magnetite compared to ZVI. HIGHLIGHTS: New experimental set-up for the in-situ monitoring of Hg 0 associated with aqueous Hg 2+ reduction by iron-based solid compounds. Hg 0 production bursts from a highly diluted HgCl2 solution (25 ng L −1 ) reacting with magnetite–zerovalent iron (ZVI) composite powder are monitored on a time-resolved basis. Magnetite and ZVI are efficient to reduce Hg 2+ in a different pH window. Graphical Abstract